PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Gany Ibrahim Fenandar; Surya Raharja (Diponegoro Journal of Accounting, 2013)
ABSTRACT The research aims to analyze the influence of investment decision, financing decision, and dividend policy on the firm value which occurred by price book value, using a data set consisting of 94 manufacturing company listed in Indonesia Stock Exchange . Population of this research is listed public company at Indonesia Stock Exchange with manufacturing company as sample. Sampling method uses purposive sampling method. Data analysis technique uses classic assumption test and Hypothesis test uses multipleregression analysis The results of this research indicate that the investment decisions positively affects the firm value, dividend policy positively affects the firm value. While the financing decisions did not significantly affects the firm value.